Pbysical Properties of Lotus Blossoms (Kamal Gatta) - Singh, Daya S; Goyal, Neeraj (Journal of Agricultural Engineering, 2004)
Investigations were carried out to find out the Physical properties of lotus blossoms at five levels of moisture content (7.5,12.5, 17.5, 22.5 and 27.5% wb). The moisture content of the procured seeds was 7.4% (wb). The physical properties (grain size, sphericity, thousand kernel weight and thousand,kernel volume) were calculated and found that grain size increased linearly whereas the sphericity first decreased upto 17.5% (wb) and then increased upto 21:5% (wb) with increase in moisture content. Bulk density and true density decreased with increase in moisture content. The porosity first decreased with increase in moisture content up to 22.5%(wb) and then increased up to 27.5% (wb). Angle of repose increased, whereas crushing strength decreased, with increase in moisture content. The coefficient of friction first increased with increase in moisture content up to 17.5% (wb) then it decreases up to 27.5% (wb).